2021
DOI: 10.1038/s41598-021-82325-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatments on superconducting properties and connectivity in K-doped BaFe2As2

Abstract: Fe-based superconductors and in particular K-doped BaFe2As2 (K-Ba122) are materials of interest for possible future high-field applications. However the critical current density (Jc) in polycrystalline Ba122 is still quite low and connectivity issues are suspected to be responsible. In this work we investigated the properties of high-purity, carefully processed, K-Ba122 samples synthesized with two separate heat treatments at various temperatures between 600 and 825 °C. We performed specific heat characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…On the other hand, the discussion suggests that the neck of the aggregate bonding needs to be extended to improve J c further. Hot isostatic pressing sintering [33] and spark plasma sintering to melt the neck under a high-pressure environment are a few possible methods to achieve the extension of aggregate bonding neck. In addition, the results of our study show that these microstructural parameters were successfully quanti ed in three dimensions and that the degree of microstructural control in Ba-122 can be organized as quantitative values in the future.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the discussion suggests that the neck of the aggregate bonding needs to be extended to improve J c further. Hot isostatic pressing sintering [33] and spark plasma sintering to melt the neck under a high-pressure environment are a few possible methods to achieve the extension of aggregate bonding neck. In addition, the results of our study show that these microstructural parameters were successfully quanti ed in three dimensions and that the degree of microstructural control in Ba-122 can be organized as quantitative values in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The very first of this class of superconducting compound, LaFeAsO 1-x F x (1111), exhibits superconductivity at 26 K. However, over several years this class of compounds has expanded considerably to a variety of families, and superconducting critical temperature been raised to 58 K for the SmFeAsO 1−x F x [ 2 ]. The BaFe 2 As 2 /SrFe 2 As 2 (122) IBS family superconductors demonstrate critical temperatures (T c ) up to 37–38 K, high upper critical magnetic field H c2 more than 100 T, low anisotropy (γ = 1–2), and high J c (about 10 6 A/cm 2 ) [ 3 , 4 , 5 , 6 ], which make them appropriate candidates for practical use [ 7 , 8 ]. The 1111 IBS family is another possible candidate for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] But to properly address the intrinsic mechanism we need to rule out the extrinsic effects caused by impurity phases introduced by processing. Indeed, recent studies have suggested that the intergrain connectivity of Ba122 can be easily degraded by extrinsic factors such as local or global impurity concentrations and GB cracks [23][24][25][26][27][28][29] that can lead to poor reproducibility of the intergrain J c . Oxygen contamination, even at low levels, degrade GB connectivity in K-Ba122.…”
mentioning
confidence: 99%
“…The number of current paths would be physically reduced by an extrinsic current blocker at the GBs, including FeAs, Ba oxide and/or nanocracks which are dependent on the synthesis and processing. 25,26,29,30,40) Concerning intrinsic current limiters, it appears highly plausible that J c across the GBs in Fe-based superconductors including Ba122 decays as a function of GB misorientation angle, 19,20) although it is still largely unknown how much reduction in J c actually occurs in the GBs of K-Ba122. Nevertheless, previous studies suggested that grain alignment such as uniaxial or concentric texturing is beneficial for raising J c , 36,39) presumably due to improvement of intrinsic GB connectivity by reducing GB misorientation.…”
mentioning
confidence: 99%